Evaluation of artificial inoculation methods to determine resistance reaction to dry root rot and black root rot disease in mulberry (Morus spp.). (2nd January 2023) - Arunakumar, Gondi S.; Gnanesh, Belaghihalli N.
Abstract: Root rot disease of mulberry is a widespread soil-borne disease, which can cause serious damage and huge economic loss to mulberry production in India. Efficient and reliable screening methods are prerequisites to evaluate the disease-resistant germplasm accessions for developing a cultivar's resistance to root rot. A multifactor experiment with four replications was established to evaluate four different inoculation techniques namely, colonized sorghum grains (CSG), colonized toothpick, root dip (RD), and syringe inoculation using pathogenic isolates of three fungal pathogens; Fusarium solani, F. oxysporum (dry root rot) and Lasiodiplodia theobromae (black root rot) against known resistant and susceptible mulberry germplasm accessions under glasshouse conditions. In addition, all the methods of evaluating resistance were compared and the results indicated that CSG and RD methods of inoculation for dry and black root rot were stable in their pathogenic effect. Also, these two methods were easy to screen and more convenient than other methods.